Social support and psychological well-being in younger and older adults: The mediating effects of basic psychological need satisfaction - Shin, Huiyoung; Park, Chaerim (Frontiers in Psychology, 2022)
This study examined the associations between social support from different relationship types (i.e., spouses, children, friends, and parents) and psychological well-being (i.e., happiness and depressive symptoms), and the mediating effects of basic psychological needs satisfaction (i.e., autonomy, competence, and relatedness) in these associations. A dataset on social support, satisfaction of basic psychological needs, and psychological well-being was collected from 823 South Korean adults (the mean of age = 48.83; 50.40% male). Results showed that social support from spouses and friends had the most robust associations with happiness and depressive symptoms. In addition, the satisfaction of needs for autonomy and relatedness mediated the associations between social support from spouses and friends, and happiness and depressive symptoms. However, these associations differed by age groups. Although social support satisfied basic psychological needs better for younger adults than for older adults, the satisfaction of needs for autonomy and relatedness was critical in order to support well-being for both groups.